Influence of Curry leaves (Murraya koenigii L.) against of bleeding time of Rattus norvegicus - Teuku Ahmad ARBI; Putri Rahmi NOVIYANDRI; Meutia FADHILA (Dentistry Faculty, 2020)
Bleeding is when blood is removed from damaged blood vessels and can occur during dental procedures. Curry leaves (Murraya koenigii L.) contain tannins and flavonoids, which have the potential as a hemostatic agent to stop bleeding. The purpose of this study was to determine the effect of curry leaf extract (Murraya koenigii L.) on the bleeding time of Wistar rats (Rattus norvegicus). The test animals used were 5 Wistar rats (Rattus norvegicus), which were divided into a control group that was applied with distilled water and the treatment group with the extract of curry leaves. The first treatment group was given a concentration of 25%, the second treatment group had a concentration of 50%, the third treatment group had a concentration of 75%, and the fourth treatment group had a concentration of 100%. Bleeding time was calculated using the Duke method on the tail of the rats. The results showed that curry leaf extract concentrations of 25%, 50%, 75%, and 100% were able to shorten the bleeding time with an average time of 140 seconds, 81.67 seconds, 138.33 seconds, and 73.33, respectively. Second. One-way ANOVA data analysis showed that the bleeding time in all treatment groups was significantly different from the control group (p 0.05). This study concludes that the extract of curry leaves (Murraya koenigii L.) affects the bleeding time in Wistar rats (Rattus norvegicus).